Analysis of deferasirox and deferipron use in children with pediatric ï¢-thalassemia major - Sutrisnaningsih, Evy Sari; Suharjono, Suharjono; Sudarmanto, Bambang (Folia Medica Indonesiana, 2017)
b-thalassemia major is a genetic disease and a decline in production due to imperfect of hemoglobin. Clinical manifestations are anemia, treated with regular blood transfusions. Blood transfusions lead to an increase in iron in the body that can lead to organ complications. Iron chelation drug delivery is expected to reduce complications due to an increase in the amount of iron in the body by measuring serum ferritin. The study aims to analyze the use of deferasirox and deferipron in patients with b-thalassemia major children at Dr. Kariadi Hospital of January 1, 2012 until December 31, 2013 as well as the need for blood transfusions. Patients who met the inclusion criteria, ie patients with b-thalassemia major children, retrospectively conducted observations of medical records include basic data and laboratory data. After descriptive analysis was performed to determine the use of two types of iron chelating drugs. In this study, 9 patients included in the inclusion criteria. A total of 5 people using deferasirox and 4 using deferipron at baseline. There are 3 people who turned deferipron be deferasirox. Serum ferritin values at study entry was> 1200 mcg/L, and at the end of the study serum ferritin is> 1200 mcg/L. The mean dose of deferasirox study was 19 ± 4.3 mg, and the dose deferipron mean was 80.8 ± 7.7 mg. Mean hemoglobin levels before transfusion was 6.60 ± 0.89 mg/dL. The average number of blood transfusions given was 336.52 ± 73.85 ml. Type of blood transfusion is used Washed erythrocyte. Splenomegaly occurred in 2 patients. There is no change in renal function, and hepatic meaning. The final conclusion until the reduction target serum ferritin <1000 mg/L has not been reached. Deferasirox dose can be increased to achieve the expected serum ferritin.